Balance the following equation: B2O3(s) + HF(l) → BF3(g) + H2O(l)
A) B2O3 (s) + 6HF(l) → 2BF3 (g) + 3H2O(l)
B) B2O3 (s) + H6F6(l) → B2F6(g) + H6O3 (l)
C) B2O3 (s) + 2HF(l) → 2BF3 (g) + H2O(l)
D) B2O3 (s) + 3HF(l) → 2BF3 (g) + 3H2O(l)
E) B2O3 (s) + 6HF(l) → 2BF3 (g) + 6H2O(l)
Frequently Asked Questions
What scientific concept do you need to know in order to solve this problem?
Our tutors have indicated that to solve this problem you will need to apply the Balancing Chemical Equations concept. You can view video lessons to learn Balancing Chemical Equations. Or if you need more Balancing Chemical Equations practice, you can also practice Balancing Chemical Equations practice problems.
What is the difficulty of this problem?
Our tutors rated the difficulty ofBalance the following equation: B2O3(s) + HF(l) → BF3(g) + H...as medium difficulty.
How long does this problem take to solve?
Our expert Chemistry tutor, Sabrina took 4 minutes and 27 seconds to solve this problem. You can follow their steps in the video explanation above.
What professor is this problem relevant for?
Based on our data, we think this problem is relevant for Professor Dixon's class at UCF.